Scalar politics, power struggles and institutional emergence in Daw Lar Lake, Myanmar - Suhardiman, Diana; Scurrah, N.; Ayemyaing, N. (Elsevier, 2021)
This paper looks at scalar politics, power struggles, and institutional emergence in Daw Lar Lake in Karen state, Myanmar. It brings to light tensions between centralized and decentralized approaches in the country’s natural resource governance, and how these are manifested in the current legal stalemate with regard to the formal management status of the lake. Building on earlier research on legal pluralism and critical institutionalism, we look at: 1) how the current legal stalemate with regard to the formal management status of the lake is rooted in ongoing bureaucratic struggles between different government agencies; 2) local communities’ strategies to develop and implement their own vision of lake governance through the formation of the Daw Lar Lake Interim Committee; and 3) the extent to which the Interim Committee is able to mediate diverse and often competing local uses and claims to natural resources at (inter) village level, which are based on a mix of customary and ‘official’ legal entitlements and normative orderings. From a policy perspective, we highlight the need to identify pathways for collective action among and across different groups of resource users, as the latter will be crucial in addressing ongoing resource competition, managing cross-sectoral livelihood impacts and ensuring sustainable lake management.